Displaced Girlhood: Gendered Dimensions of Coping and Social Change among Conflict-Affected South Sudanese Youth - Ensor, Marisa O. (Refuge: Canada’s Journal on Refugees, 2014)
As wartime inhabitants, female children have often been presented as paradigmatic non-agents, victims of a toxic mixture of violent circumstances and oppressive cultural practices. Child- and gender-sensitive approaches, on the other hand, have embraced a more balanced recognition of displaced girls’ active, if often constrained, efforts to cope with adverse circumstances. In South Sudan, a young country mired in unresolved conflict and forced displacement, girls must navigate multiple and complex challenges. Drawing on fieldwork conducted among South Sudanese refugees in Uganda and returnees in South Sudan, I examine ways in which gender shapes local realities of conflict, displacement, return, and reintegration, focusing on the often-overlooked experiences of girls and female youth. Study findings evidence displaced girls’ remarkable determination and resourcefulness as they struggle to overcome a persistently turbulent climate of social instability, deprivation, and conflict.